Application of multiple occupational health risk assessment models in the prediction of occupational health risks of n-Hexane in the air-conditioned closed workshop - Zhu, Jiawei; Su, Shibiao; Wen, Cuiju; Wang, Tianjian; Xu, Haijuan; Liu, Ming (Frontiers in Public Health, 2022)
Background n-Hexane (NH) poisoning is a common occupational poisoning in the hardware and electronics industries. However, there is few research data on risk assessment of positions using NH in enclosed workshops. It is very important to assess the risk level of these positions and put forward effective measures and suggestions. Methods The information of selected companies and air samples were collected through on-site investigation, and data collation and sample testing were carried out according to the requirements of Chinese standards. The Control of Substances Hazardous to Health (COSHH) Essential, the EPA non-carcinogenic risk assessment model, the Singapore exposure index method and the Chinese semi-quantitative risk assessment models were used to assess the risks of NH. Results The working hours of the exposure groups, printing groups and packing groups all exceeded 9 h per day, less than 30% of each similar exposure groups (SEG) was equipped with the local exhaust ventilation, and 11.1% of the cleaning group and 8.3% of the printing group had NH concentrations in the air that exceeded the Chinese occupational exposure limit (OEL). In the EPA non-carcinogenic risk assessment model, each SEG was evaluated at high risk. In the Chinese semi-quantitative risk assessment models, all of the work groups of exposure groups, 91.7% of the work groups of printing groups, 77.8% of the work groups of printing groups, and 57.1% of the work groups of printing groups were evaluated at unacceptable risk. More than 40.0% of the work groups of printing groups and cleaning groups and over 20.0% of the work groups of exposure groups and packing groups were evaluated at high risk in the Chinese semi-quantitative risk assessment models. Conclusions The Chinese exposure index method and the synthesis index method may have a stronger practicability. Some work groups that use NH in air-conditioned enclosed workshops in China, especially the cleaning groups, are still in a high-risk state. It is necessary to increase protective measures and strengthen occupational hygiene management to reduce risks.